Concise rules of APA style. - American Psychological Association (Washington, DC : American Psychological Association, 2010)
This easy-to-use pocket guide, compiled from the sixth edition of the "Publication Manual of the American Psychological Association," provides complete guidance on the rules of style that are critical for clear communication.
Concise and bias-free writing -- Punctuation, spelling, and capitalization -- Italicizing and abbreviating -- Numbers, metrication, and statistics -- Displaying results -- Footnotes, appendices, and supplemental material -- Crediting sources -- Reference examples -- Appendix 8.1: References to legal materials.
Includes bibliographical references and index.
Keywords: Psychology -- Authorship -- Style manuals; Social sciences -- Authorship -- Handbooks, manuals, etc; Writing -- standards; Authorship; Handbooks